1991
DOI: 10.1159/000186274
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Flow Cytometry for Cross-Match Evaluation in Clinical Renal Transplantation

Abstract: This paper reports a 2-year experience of more than 5,000 cross-match tests for renal transplantation. Tests were performed by means of both standard light microscopy and an innovatory method based on now cytometry, an up-to-date investigative technique for computerized analysis of individual cell characteristics. Flow cytometry allowed a better detection of weak positive reactions (false-negative cross-matches) than light microscopy, thus reducing the risk of selecting candidates with donor presensitization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…Until now, this latter category of complement fixing HLA antibodies has gone unrecognized. This may simply be the result of enhanced fluorescence detection by instrumentation rather than by visual inspection similar to that that described by Stefoni et al (18). Alternatively, since all cells were pronase treated we cannot discount the possibility that pronase removed anti-complementary surface proteins such as decay accelerating factor thereby enhancing the cytolytic activity of complement.…”
Section: The Cfcxm Assaymentioning
confidence: 91%
“…Until now, this latter category of complement fixing HLA antibodies has gone unrecognized. This may simply be the result of enhanced fluorescence detection by instrumentation rather than by visual inspection similar to that that described by Stefoni et al (18). Alternatively, since all cells were pronase treated we cannot discount the possibility that pronase removed anti-complementary surface proteins such as decay accelerating factor thereby enhancing the cytolytic activity of complement.…”
Section: The Cfcxm Assaymentioning
confidence: 91%
“…Similarly, for regrafts one would need 357 patients per group to show a 10% survival advantage assuming a current cadaver regraft survival of 264 Sridhar/M unda/Balakrishnan/First Flowcytometric Crossmatching in Renal Allograft Recipients Several small studies have indicated a worse outcome in FCXM-positive patients with regard to the total number of rejection episodes [4,II], overall graft survival [2,5], early rejection episodes [4,11,12] and graft loss [7,11]. The largest group of FCXM-positive and -negative patients has been reported by the UCLA Tissue Typing Laboratory [6,8,15,16]. In their analysis of 1,060 FCXM-negative first cadaver transplants, 202 FCXM-positive first transplants, 134 FCXM-negative second transplants and 59 FCXM-posi tive second transplants, the 3-month, 6-month and 1-year graft survival was significantly lower in the FCXM-positive regrafts (p < 0.01) compared to the other three groups at all time points [15].…”
Section: Discussionmentioning
confidence: 99%
“…Efforts are continuing to identify re cipients at risk for allograft rejection. The sensitive method of flowcytometry has been used to identify patients with antibodies to donor lymphocytes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Most studies indi cate a poor outcome in regrafts when the recipient is posi tive by flowcytometric crossmatch (FCXM) testing.…”
Section: Introductionmentioning
confidence: 99%
“…In [9] and [13] a new flow cytometry method for cross-match evaluation has been proposed. This method allows a better detection of weak positive reactions than the light microscopy.…”
Section: Future Development Of the Subsystemmentioning
confidence: 99%